PEMBERDAYAAN SOSIAL EKONOMI MASYARAKAT PINGGIRAN KOTA SURABAYA, KOMUNITAS KELUARGA KB VASEKTOMI SIWALAN MESRA DI KECAMATAN PAKAL [THE SOCIAL ECONOMY EMPOWERMENT OF SURABAYA CITY EDGES COMMUNITY, SIWALAN MESRA VASECTOMY FAMILY PLANNING COMMUNITY IN PAKAL DISTRICT] - Nurleila Jumati; Tri Siwi Agustina; Prita Anugrah Widowati (Jurnal Sinergitas PKM & CSR, 2019)
The Siwalan Mesra community is a community that consists of family members who joint Vasectomy birth control. From 50 Vasectomy birth control families in Pakal Subdistrict, the western outskirts of Surabaya, data shows 24% of pre-prosperous families, 40% of prosperous families I, 18% of prosperous families II, 4% of prosperous families III, 14% of prosperous families III plus. Taking from depth interview, it was obtained additional data that 34% or 17 families had businesses, both the main business and additional businesses carried out by the wife and or family to support family income. These businesses include businesses in food production, trade, and services. The problems faced are: the business carried out by vasectomy families does not yet have a standardized product and the legality, in this case is SIUP. The purpose of the empowerment carried out is standardization of food products and SIUP management assistance. The method used in the empowerment of the Vasectomy family planning is socialization, training, industrial visits, and SIUP management assistance. The results obtained in the program are improving product quality by applying standardization and the issuance of 17 SIUP.